Local Newspaper Decline and Political Polarization – Evidence from a Multi-Party Setting - Fabio Ellger; Hanno Hilbig; Sascha Riaz; Philipp Tillmann (British Journal of Political Science, 2024)
How does the decline of traditional news outlets affect political polarization? We provide novel evidence on this question by examining the link between local newspaper exits, media consumption, and electoral behaviour in a multiparty setting. Our empirical analysis combines a unique panel of all German local newspapers between 1980 and 2009, electoral returns, and an annual media consumption survey of more than 670,000 respondents. Using a difference-in-differences design, we demonstrate that local newspaper exits increase electoral polarization. Additional analysis points to changes in media consumption as the underlying mechanism driving this result: following local news exits, consumers substitute local news with national tabloid news. Our findings extend prior results in the US context to a multiparty setting and shed new light on the causal chain running from changing local news landscapes to electoral behaviour.
https://doi.org/10.7910/DVN/MD0UYZ
Keywords: 320; polarization; local news decline; newspapers; media consumption